(untitled) (American Journal of Life Science and Innovation, 2024)
The study aimed to explore the art of pedagogy in teaching linear programming to support novice performance. The study was qualitative in nature and hermeneutic phenomenological design guided the study. The study had 16 participants who were selected through homogenous purposive sampling. Data was produced through semi-structured interviews and focus group discussion schedules. Then generated data was thematically analysed. Findings of the study were that Comprehensive Pedagogy has been essential to secondary school students’ academic achievement and advancement. Comprehensive pedagogy is typically demonstrated by the teaching strategies used to improve learning and the resources used in the teaching/learning process. However, most teachers were not employing appropriate methods in teaching linear programming hence poor pupils performance. Freeman et al. (2014) supports the use of group work in the teaching/learning process since it encourages students’ social inclusion. Make use of interactive techniques such as problem-solving workshops, case studies, and group discussions. Participation is encouraged and newcomers can apply LP ideas realistically with the aid of interactive learning. On approaches to problem-solving, offer constructive criticism. Beginners should apply LP techniques with plenty of possibilities to practice on a regular basis.